Developing as an Academic Leader in a University of Technology in South Africa: Dealing with enabling and constraining teaching and learning environments - Monnapula-Mapesela, Mabokang (Critical Studies in Teaching and Learning, 2023)
While the South African legislation is an enabler for equity, inclusiveness, social justice and the advancement of women for academic leadership roles, institutional cultures and structures are often debilitating. This paper presents the development trajectory of a Black woman as an academic development leader in a South African University of Technology. It examines structural and cultural factors acting as enablers or constraints to leadership development and career advancement for Black women. It analyses dominant structural frames and undertakings of different University stakeholders (agents), which cause stagnation and resistance to morphogenesis and government’s transformation agenda. Using Participatory Narrative Inquiry (PNI), I narrate personal experiences and insights as a participant researcher. I interrogate the experiences, observations and influence of various structural and cultural modalities within Margaret Archer’s (1995) social realist framework of structure, culture and agency. I highlight the implications of these for development of a Black female academic development leader.